Hydration of a-pinene over molybdophosphoric acid immobilized in hydrophobically modified PVA membranes - Castanheiro, José (2012)
A polyvinylalcohol/molybdophosphoric acid (PVA/HPMo) membrane crosslinked with succinic acid was modified by treatment with acetic anhydride in order to improve its hydrophobic properties, and was used as catalyst in the hydration reaction of a-pinene. The increase of membrane hydrophobicity with acetylation is documented not only by the water droplet contact angle but also by the sorption coefficients of a-pinene and water. The introduction of acetyl groups improves the membrane transport properties, as reflected by pinene diffusivity calculated from permeation data. A kinetic-diffusion model was developed assuming that the reaction product a-terpineol affects the transport of water and a-pinene across the acetylated PVA membranes. When membrane acetylation increases, the model predicted kinetic constants for hydration and isomerization reactions decrease, although the initial water diffusivity increases. These results suggest that the increase of catalytic activity may be due to an improvement of water transport across the membrane.